Impacts of demographic, meteorological, and economic changes on household CO2 emissions in the 47 prefectures of Japan1. Issue 1 (2nd May 2013) - Honjo, Keita; Fujii, Masahiko
Abstract An understanding of the factors affecting household CO2 emissions is necessary for effective climate policies aimed at reducing emissions. We developed an empirical model of household CO2 emissions in the 47 prefectures of Japan and conducted a sensitivity analysis to evaluate the impacts of demographic, meteorological, and economic changes on emissions. Emissions are projected to increase with demographic changes by 2030, and to decrease with temperature increases during the twenty‐first century. Carbon taxes on energy sources are projected have a limited effect on the reduction of emissions in the short term. The closure of nuclear power plants is projected to lead to a substantial increase in emissions.